KEPATUHAN TERHADAP PERATURAN KESELAMATAN DAN KESEHATAN KERJA (K3) HUBUNGANNYA DENGAN KECELAKAAN KERJA - Linda NurAini; Ratih Sari Wardani (Jurnal Kesehatan Masyarakat Indonesia, 2015)
Background: work accident still being happened in industrial affairs Including in PT.Coca cola amatil indonesia central java, altough it was OHS management. Submissive was the one of work accident causes. Report of the work accidents and occupational diseases of The Coca Cola Amatil Indonesia Company in Central showed 18 accidents happened in 2013, consist of 4 light accidents and 14 medium accident and also 362 occupational diseases. The causes of accidents work influenced by three factors them are factor workers, factor work and environmental factors. Objective: To know is there any correlation between submissive to occupational health and safety regulation with work accident. Method: This type of research was analytical with cross sectional approach. Population were 40 workers of production part. Independent variable was submissive to OHS and dependentvariable was work accident. Data analyzed by Chi Square.Result : Submissive to OHS of the workers is very good (60%), accident work experienced (17,5%), but there was no correlation between between submissive to occupational health and safety regulation with work accident p=0,407. Result: Submissive to OHS of the workers is very good (60%), accident work experienced (17,5%), but there was no correlation between betweensubmissive to occupational health and safety regulation with work accident p=0,407. Conclusion: There was no correlation between submissive to occupational health and safety regulation with work accident